2020
DOI: 10.1137/19m1268641
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Properties of Barzilai--Borwein Rules in Solving Singly Linearly Constrained Optimization Problems Subject to Lower and Upper Bounds

Abstract: In 1988, Barzilai and Borwein published a pioneering paper which opened the way to inexpensively accelerate first-order. In more detail, in the framework of unconstrained optimization, Barzilai and Borwein developed two strategies to select the step length in gradient descent methods with the aim of encoding some second-order information of the problem without computing and/or employing the Hessian matrix of the objective function. Starting from these ideas, several efficient step length techniques have been s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Numerical experiments on minimizing quadratic functions (4) show that our method performs much better than the most successful gradient methods developed in recent literature including BB1 [1], Dai-Yuan (DY) [14], ABB [46], ABBmin1 [20], ABBmin2 [20] and SDC [16]. In addition, numerical comparisons of our method with the spectral projected gradient (SPG) method [2,3] on box-constrained problems from the CUTEst collection [24] and with the Dai-Fletcher [11] and EQ-VABBmin methods [7] on random SLB problems and SLB problems arising in support vector machine (SVM) [6] highly suggest the potential benefits of our new proposed method for solving general box-constrained and SLB optimization problems.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…Numerical experiments on minimizing quadratic functions (4) show that our method performs much better than the most successful gradient methods developed in recent literature including BB1 [1], Dai-Yuan (DY) [14], ABB [46], ABBmin1 [20], ABBmin2 [20] and SDC [16]. In addition, numerical comparisons of our method with the spectral projected gradient (SPG) method [2,3] on box-constrained problems from the CUTEst collection [24] and with the Dai-Fletcher [11] and EQ-VABBmin methods [7] on random SLB problems and SLB problems arising in support vector machine (SVM) [6] highly suggest the potential benefits of our new proposed method for solving general box-constrained and SLB optimization problems.…”
Section: Introductionmentioning
confidence: 86%
“…Both the above two schemes adopt short and long stepsizes, and perform better than using only one type of stepsize. Variants and other stepsize rules can be found in [4,7,9,20,21,29,37]. It has been observed that replacing α BB2 k with a short stepsize will further improve the performance of the adaptive scheme [8,20,29].…”
Section: A New Methods For Quadraticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our techniques are based on the so-called cartoon-texture decomposition of the given image, on the mean and median filters, and on a thresholding technique. The resulting locally adaptive segmentation model can be solved either by smoothing the discrete TV term-see, e.g., [16,17]-and applying optimization solvers for differentiable problems, such as spectral gradient methods [18][19][20][21], or by using directly optimization solvers for nondifferentiable problems, such as Bregman, proximal and ADMM methods [22][23][24][25][26][27][28]. In this work, we use an alternating minimization procedure exploiting the split Bregman (SB) method proposed in [24].…”
Section: Introductionmentioning
confidence: 99%